2020
DOI: 10.1186/s12888-020-02658-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with depressive and anxiety symptoms among Palestinian medical students

Abstract: Background: Coexistence of depression and anxiety can be associated with severe detrimental consequences to the physical, mental and social wellbeing of the affected populations. This study was conducted to determine prevalence of depressive and anxiety symptoms among Palestinian medical students and to investigate associations between sociodemographic factors of the students with depressive and anxiety symptoms. Methods: This study was conducted in a cross-sectional observational design using a questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
45
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 64 publications
13
45
0
3
Order By: Relevance
“…In this study, the response rate was 91.0%. The response rate obtained in this study was high when compared to response rates reported in previous studies in which a questionnaire was used as a study tool among healthcare providers including nurses [ 39 , 41 , 48 , 52 ]. Interestingly, the number of nurses who responded to the questionnaire was larger than the sample size needed for this study.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…In this study, the response rate was 91.0%. The response rate obtained in this study was high when compared to response rates reported in previous studies in which a questionnaire was used as a study tool among healthcare providers including nurses [ 39 , 41 , 48 , 52 ]. Interestingly, the number of nurses who responded to the questionnaire was larger than the sample size needed for this study.…”
Section: Discussionmentioning
confidence: 49%
“…The nurses were also asked to self-rate their satisfaction with their financial status, social status, academic achievements, and perceived knowledge about COVID-19 using a Likert-scale of 1–3 (1 = low, 3 = high). Previous studies have shown that satisfaction with financial status, social status, and academic achievements were associated with knowledge, attitudes, and behaviors [ 48 ]. During the ongoing pandemic, many healthcare centers suffered shortages of personal protective equipment and healthcare providers had to purchase their own sanitizers, gloves, masks, and other personal protective equipment [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, they have shown signs and symptoms of anxiety due to uncertainty and the negative academic impact on the development of their classes. [ 15 22 , 28 ] Anxiety as a mechanism of physiological response to danger may increase due to a permanent feeling of insecurity or excessive fear, especially in these times of COVID-19 pandemic. This disease has been reported to be highly transmissible, to the extent that an infected person could infect up to five or six people around them ( R 0 = 5.7; 95% CI: 3.8–8.9) in a period of 6–9 days.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Some research has shown that medical science students are the most likely to suffer from anxiety symptoms. According to the authors,[ 18 19 20 21 22 ] there are various sociodemographic factors that can increase worries, stress, and their anxiety levels.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 9.1% had severe depression. 12 According to the previous studies, depression rates in first-year medical students are higher when compared to the year after. This statement is supported by a study in Portugal which showed a depression rate of 72.5% in the first year, 29.1% in the second year and 54.9% in the third year.…”
Section: Discussionmentioning
confidence: 95%